1976
DOI: 10.1021/jo00876a006
|View full text |Cite
|
Sign up to set email alerts
|

Fulvenes and thermochromic ethylene. 88. Stabilization of cyclopropenium ion and cyclopropenone by guaiazulene

Abstract: Stabilization of Cyclopropenium Ion by Guaiazulene l-Methoxy-l,2-dichloro-2,3,3-trifluorocyclopropane (2). A solution of 24.8 g (0.2 mol) of la in 100 ml of methylene dichloride was protected from the light and treated slowly with 14.2 g (0.2 mol) of precondensed chlorine while keeping the reaction temperature below 0 °C. After stirring in the dark at room temperature overnight, the reaction mixture was distilled at atmospheric pressure to remove the solvent, and the residual oil was fractionated in vacuo to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Starting from formyl ferrocene and azulenes as precursors, the yields of products 24n were between 58% and 68% (Scheme 19). Contrary to the very low stability of most carbocations with hydrocarbon skeleton, some cyclic cations such as cyclo-propenyl [52] have remarkable stability. In fact, this system is the simplest aromatic Hückel system.…”
Section: Other Systems Stabilized By Azulen-1-yl Moietiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Starting from formyl ferrocene and azulenes as precursors, the yields of products 24n were between 58% and 68% (Scheme 19). Contrary to the very low stability of most carbocations with hydrocarbon skeleton, some cyclic cations such as cyclo-propenyl [52] have remarkable stability. In fact, this system is the simplest aromatic Hückel system.…”
Section: Other Systems Stabilized By Azulen-1-yl Moietiesmentioning
confidence: 95%
“…Salt 23 was obtained by condensation of all-trans-retinal with azulenes (Scheme 18) [50]. Considering the good electron donor property of both ferrocene and of azulen-1-yls, Farrell et al [52] used ferrocene-azulenium carbocations and their vinyl-ogs as tetrafluoroborates to investigate a novel series of monometallic monocations, 24n. Starting from formyl ferrocene and azulenes as precursors, the yields of products 24n were between 58% and 68% (Scheme 19).…”
Section: Other Systems Stabilized By Azulen-1-yl Moietiesmentioning
confidence: 99%
“…It was expected that, for cation 15 , first synthesized by Agranat and Aharon-Shalom, 24 the three guaiazulenyl groups would effectively raise the thermodynamic stability of the cation and also increase steric congestion around the positive charge. Its pK R value of 13.6 25 ranks it as one of the most stable hydrocarbon cations known today.…”
Section: Hydrocarbon Saltsmentioning
confidence: 99%
“…Agranat reported that the p K R + value of 2 + is greater than 10 in 50% aqueous acetonitrile by potentiometric titration (ref ). We determined the p K R + value by spectrophotometrical titration of a glycine-buffered solution of 2 + ClO 4 - in 50% aqueous acetonitrile with aqueous NaOH.…”
Section: Referencesmentioning
confidence: 99%